Flexibly actuated pneumatic extrusion with in-situ monitoring for direct ink writing of heterogeneous and pressure-vulnerable materials - Chaiwuth Sithiwichankit; Setthibhak Suthithanakom; Kantawatchr Chaiprabha; Kai Melde; Ratchatin Chancharoen (Scientific Reports)
Abstract This study presents a novel piston-driven pneumatic extrusion system for direct ink writing (DIW), featuring flexible actuation and real-time monitoring of extrusion pressure. The design integrates the benefits of both pressure and feedrate control, achieving consistent linewidth while safeguarding pressure-sensitive materials such as cell-laden hydrogels. The system comprises a lightweight pneumatic syringe on the printhead and a stationary actuation unit, allowing efficient decoupling of motion and extrusion. Experiments demonstrate stable gelatin extrusion with a mean linewidth of 4.32 mm and a minimal increase ratio of 0.012 over printing distance. These findings show promise for advancing DIW with emerging soft materials, particularly in bioprinting and sustainable manufacturing.